The National Estate (and the city), 1969–75: a significant Australian heritage phenomenon. Issue 2 (1st February 2019) - Lesh, James P.
ABSTRACT: This article argues that the Australian Whitlam Labor Government between 1969 and 1975 produced a distinguishably Australian conception for heritage through its notion of the national estate. A watershed for the recognition and preservation of heritage in Australia, it was expansive, democratic and interventionist in its philosophical underpinning and approach. Focusing on the domain of urban heritage and drawing on a diverse range of archival sources, this article examines the national estate's international origins, along with its reworking by Whitlam, his inner circle and the Inquiry into the National Estate (1973–4). The national estate reshaped public, management and regulatory understandings of heritage in Australia, and informed the Australian Heritage Commission (1975 –2004) and the Burra Charter (1979), leaving lasting local and global impacts.